Looking Back, Looking Forward: Canadian Higher Education Research on Tuition Fees - Rexe, Deanna; Maltais, Martin (Canadian Journal of Higher Education, 2022)
To contribute to the 50th Anniversary Issue, this scholarly article will review the literature on Canadian higher education tuition fees over the past 50 years, focusing on the major theme of higher education planning, and the role higher education research has played in the policy-making environment. Examining both the French and English language scholarship published by the CJHE, the researchers will describe the contributions, and provide commentary on opportunities for impactful research for the future. Presenting a case study in Québec, the article will identify emerging trends that are anticipated to shape this higher education policy area in the future.